Analysis of Word of Mouth as a Marketing Communication Strategy of Dj Arie Public Speaking and Broadcasting Schools on Social Media Instagram - Putri Nabilah Anjani; Ratih Hasanah Sudradjat (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
Communication skills are very important when carrying out marketing activities. Communication can affect the results of marketing which of course will be related to product sales issues. Marketing communication is a determining factor for success and is a marketing program that is carried out. With the various benefits obtained through the WOM marketing communication strategy, this is related to what was carried out by one of the Public Speaking and Broadcasting Schools in Bandung. As a media sharing in conveying various matters regarding the Science of Public Speaking and Broadcasting. as done by DJ Arie School. In this study, the paradigm used is the post positivism paradigm. In collecting the data, the writer uses observation, interview, documentation, and triangulation techniques. The data that the researcher has obtained is then processed and analyzed, so that the researcher can explain how Word of Mouth is a Marketing Communication Strategy for Dj Arie Public Speaking and Broadcasting School on Instagram Social Media. Based on the research results, it is known that Dj Arie Public Speaking and Broadcasting School has paid close attention to the three elements of the Marketing Communication Strategy. Then Word of Mouth was carried out where services, testimonials and informative information systems were very concerned by Dj Arie School so that consumers who were satisfied because the services provided would allow them to provide recommendations for Dj Arie School to the public